Aspergillus decontamination in hazelnuts: Evaluation of atmospheric and low-pressure plasma technology. (June 2019) - Sen, Yasin; Onal-Ulusoy, Baran; Mutlu, Mehmet
Abstract: The decontamination effects of non-thermal atmospheric-pressure (AP) and low-pressure (LP) plasma systems were investigated on hazelnuts artificially contaminated with Aspergillus parasiticus and Aspergillus flavus spores. Furthermore, AP-plasma treatment conditions were also optimized. Spore reductions of 5.6 and 4.7 log cfu/g in Aspergillus parasiticus and Aspergillus flavus, respectively, were achieved after 100 W-30 min of LP-air-plasma treatment. Similarly, 5.5 and 5.4 log cfu/g of reductions in Aspergillus parasiticus and Aspergillus flavus, respectively, were achieved after AP-air-plasma treatment at 3000 L/h of gas flow rate, frequency of 25 kHz and reference voltage of 100% (655 W) for 5-cycles (1.7 min). Deformation of spores and loss of spore integrity after plasma treatments were demonstrated with scanning electron microscope (SEM). This study showed that LP and AP plasma treatments might be an alternative method for inactivation of aflatoxin- producing fungi. Industrial relevance: Non-thermal (cold) plasma is a promising technology for decontamination of foods due to its safety, ease of use and low temperature processing capability. The results of this study showed that plasma system can be incorporated into a food processing chain, and when initial Aspergillus spp. spores were 7.8–7.9 cfu/g in hazelnut, plasma treatment with reductions of up to 5.6 log cfu/g can compete with other decontamination methods. Highlights: Contamination and growth of aflatoxin-producing fungi are a major problem for hazelnuts. Spores of Aspergillus parasiticus were reduced by 5.6 log cfu/g using low pressure (LP) air plasma. Spores of Aspergillus flavus spores were reduced by 5.4 log cfu/g after treatment with atmospheric pressure (AP) air plasma. SEM micrographs showed complete deformation of spores after treatment from the LP and AP air plasmas.